PENGARUH METODE PEMBELAJARAN DEMONSTRASI TERHADAP KETERAMPILAN PROSES SAINS PADA SMP ISLAM SA’ADATUDDARAIN NW MAJUWET LOMBOK TIMUR TAHUN PELAJARAN 2018/2019 - Edi Satria Watoni; Muhammad Zulhariadi; Rustam Rustam (PENBIOS: JURNAL PENDIDIKAN BIOLOGI DAN SAINS, 2019)
The purpose of this study was to determine the effect of demonstration learning methods on science process skills in the Islamic Middle School of Sa'adatuddarain NW Majuwet 2018/2019 Academic Year. The type of research is a Quase Experiment Pre-Exprimental Design, which uses a pre-Test and Post-Test Group. In this study observations were made 2 times, namely before the experiment and after the experiment. Observations made before the experiment (O1) are called pre-tests, and observations after the experiment (O2) are called post-tests. The sample in this study was class VII. Data collection methods in this study used tests, interviews and observation. Data analysis of the results of this study is to use the t-test, which is to test the hypothesis. The results showed that there was an effect of demonstration learning methods on science process skills, this can be seen from the results of the t-test, namely tcount = 8,197 while ttable = 1,706 (tcount> ttable) with a significant level of 0.05, so that HO was rejected and Ha was accepted . The conclusion from the results of this study is that there is a significant influence of the use of demonstration learning methods on science process skills in Sa'adatuddarain Middle School NW Majuwet East Lombok 2018/2019 Academic Year.